A New Method for the Analysis of Non-Isothermal Thermo-Analytical Data from Solid State Reaction - S., Maitra; A. K., Bandyopadhyay; N., Bandyopadhyay; J., Pramanik (INDIAN CERAMIC SOC, CENTRAL GLASS & CERAMIC RES INST, KOLKATA, 700 032, INDIA, 2009)
The existing methods for the determination of kinetic parameters of solid state reactions from non-isothermal thermoanalytical data suffer from some limitations due to inexact solution of the Arrhenius temperature integral and non-consideration of the temperature dependence of pre-exponential factor. In the present paper a new method was developed for the evaluation of kinetic parameters of solid state reactions using Gauss's quardature rule with Radau integration with a computer programme. The method was applied to determine the kinetic parameters for the decomposition reactions of MgCO3 and CaCO3 from non-isothermal thermogravimetric study.